Immunological interactions of virus peptides at the antigen presenting MHC I proteins - Rashidian, Azam (My University, 2018)
Regarding the recent outbreak of Zika virus (ZIKV) infection, there is an urgent need to develop a preventive or a therapeutic ZIKV vaccine. In this thesis, computational analysis was performed to predict suitable peptide candidates for vaccine design. Computational approaches such as docking and molecular dynamics simulations (MD simulations) were employed to evaluate the binding energy and stability of candidate T-cell epitope peptides of ZIKV proteins at the antigen-presenting MHC class I molecules. For the docking step and the following MD simulations, MHC I alleles HLA-A*0101, HLA-A*0201, HLA-B*2705 and HLA-C*0801 were used as receptor structures and eight different peptides from ZIKV proteins (E, NS3, NS5) were docked to the MHC I molecules. All predicted peptide-HLA complexes and experimental reference peptide-HLA complexes were submitted to a 10-ns MD simulation in explicit water for further refinement and to examine and compare their stability. Hydrogen bonding network, Root-Mean-Square Deviation (RMSD) for both the MHC I peptide-binding domain and the peptides, atomic fluctuation and solvent accessibility of the bound peptides, interaction energies and the dimensions of the peptide binding groove were analyzed to evaluate the stability and strength of the peptide-HLA complexes. The computational analysis provided two T-cell epitopes from the ZIKV proteins (GLDFSDLYY, FSDLYYLTM) with a high affinity to the studied MHC I alleles. These could be introduced as putative candidates for vaccine development.
Keywords: Antigenic epitope, Binding energy, HLA, MHC I molecule, Molecular dynamics simulation, Peptide docking, T-cell, Zika infection